Students' coping with the self-regulatory demand of crisis-driven digitalization in university mathematics instruction: do motivational and emotional orientations make a difference?. (July 2021) - Reinhold, Frank; Schons, Christian; Scheuerer, Sarah; Gritzmann, Peter; Richter-Gebert, Jürgen; Reiss, Kristina
Abstract: The COVID-19 pandemic induced a radical shift from face-to-face lectures to online learning in university mathematics instruction, which confronted students with a high self-regulatory demand. We investigated the role of students' motivational and emotional orientations regarding mathematics in coping with this demand. Among N = 123 university students (54 women) studying mathematics at the tertiary level, two clusters differing in mathematics related interest, anxiety, self-concept, and work ethics could be identified—namely less promising ( n = 63) and more promising ( n = 60) motivational and emotional orientations. Controlling for gender and general attitude towards learning mathematics with information and communications technology (ICT), students in the more promising cluster reported higher expectation of success, higher need for face-to-face social interaction, and less preference for online learning formats after the pandemic situation than students from the less promising cluster. However, students in different clusters did not differ significantly in their subjective task value, their learning outside of course structures, and their appreciation of digital learning formats. The results suggest that a positive general attitude towards learning with ICT was the key element influencing students' coping with learning in the pandemic situation. In addition, particularly students demonstrating more promising orientations were eager to return to face-to-face instruction. Highlights: Students clustered into two groups differing in mathematics related interest, anxiety, self-concept, and work ethics. Expectation of success, need for face-to-face social interaction, and preference for online learning formats differed. Subjective task value, learning outside of course structures, and appreciation of digital learning formats did not differ. Positive attitude towards learning with ICT was a key element for coping with learning in the pandemic situation. Particularly students demonstrating more promising orientations were eager to return to face-to-face instruction.